Peran Guru Dalam Mengembangkan Keterampilan Abad 21 Siswa Sekolah Dasar - Anti Muthmainnah; Amalia Dwi Pertiwi; Tin Rustini (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted with the aim of analyzing and knowing more deeply the extent of the teacher's role in developing 21st century skills in elementary school students. In this research study, the method used is qualitative or descriptive approach. Which theory or basic discussion is obtained from the results of literature studies from various relevant sources such as books, journals, and articles. The results of the discussion are that the teacher's role is very influential in being able to improve the skills of 21st century elementary school students with teachers having to be able to reinvent and work hard to create meaningful learning for students.